Diiron butane-1, 2-dithiolate complexes with tris(4-chlorophenyl)phosphine or tris(4-methoxyphenyl)phosphine: synthesis, characterization, X-ray crystal structures, and electrochemistry. (3rd March 2020) - Lin, Hui-Min; Wang, Ling-Hui; Li, Xie; Li, Ao; Xiao, Qi-Min; Liu, Xu-Feng; Li, Yu-Long; Liu, Xing-Hai; Jiang, Zhong-Qing
Abstract: Two diiron butane-1, 2-dithiolate complexes containing tris(4-chlorophenyl)phosphine or tris(4-methoxyphenyl)phosphine have been prepared and characterized. Treatment of complex [Fe2 (CO)6 μ -SCH2 CH(CH2 CH3 )S] (1 ) with tris(4-chlorophenyl)phosphine or tris(4-methoxyphenyl)phosphine in the presence of Me3 NO · 2 H2 O as the oxidizing agent gave the complexes [Fe2 (CO)5 P(4-C6 H4 Cl)3 µ -SCH2 CH(CH2 CH3 )S) (2 ) and [Fe2 (CO)5 P(4-C6 H4 OCH3 )3 µ -SCH2 CH(CH2 CH3 )S)] (3 ) in 92% and 90% yields, respectively. Both complexes were characterized by elemental analysis, IR, NMR spectroscopy, and their structures were confirmed by single-crystal X-ray diffraction analysis. Moreover, the electrochemical properties of complexes 2 and 3 were investigated by cyclic voltammetry. Graphical Abstract: